Karakteristik dan Potongan Komersial Karkas Domba Muda Umur Lima Bulan dengan Ransum Komplit yang Disuplementasi Minyak Bunga Matahari: Characteristic and Commersial Cutting of Five Months Young Sheep Carcass that Fed by Complete Ration Contained Sunflower Seed Oil - Lilis Khotijah; Tuti Suryati; M Fandi (Jurnal Ilmu Nutrisi dan Teknologi Pakan, 2019)
The aim of the study was to evaluate the effect of graded levels of sunflower seed oil (SSO) supplementation on lamb five-month-old carcass characteristics and commercial cuts. Used 18 local male lambs, weaned, aged about 2 months, weight (10.21 ± 2.29 kg). Experimental design used group random design. Each group of sheep get a complete ration with a different level of sunflower seed oil (SSO), namely (P0) = 0% SSO (control); (P1) = 4% SSO; (P2) = 6% SSO. After animal five old age or 90 days feeding, randomly selected tree animals from each group were slaughtered The measured parameters include, weight slaughter, carcasses composition (meats, bones, fats), and commercial cuts of carcasses (leg, loin, shoulder, breast, neck, shank, flank, rack). The observation showed that the parameters are not affected by the treatment. It can be concluded that the addition of 6% sunflower oil in a complete ration keeping the characteristics and commercial cut of local lamb. Key words: slaughter weight, carcass composition, lamb, sunflower seed oil DAFTAR PUSTAKA [AUS-MEAT]. 2005. Sheep Meat. ISBN 0 9578793 69. https://www.ausmeat.com.au/media/1275/9-sheepmeat.pdf. Diunduh 15 Juni 2019. [BSN] Badan Standardisasi Nasional Indonesia. 2008. Mutu Karkas dan Daging Kambing/Domba. Standar Nasional Indonesia. 3925. Jakarta (ID): Badan Standardisasi Nasional Indonesia [NRC] National Research Council. 2007. Nutrient Requirements of Small Ruminants: Sheep, Goats, Cervids, and New World Camelids. Washington DC (US): The National Academies Pr. Ensminger M E. 2002. Sheep and Goat Science. Illinois (US): Interstate Publisher. Francisco A, Dentinho MT, Alves SPP, Portugal V, Fernandes F, Sengo S, Jerónimo E, Oliveira MA, Costa P, Sequeira A, Bessa RJB, Santos-Silva J. 2015. Growth performance, carcass and meat quality of lambs supplemented with increasing levels of a tanniferous bush (Cistus ladanifer L.) and vegetable oils. Meat Science. 100, p. 272-282. https://doi.org/10.1016/j.meatsci.2014.10.014 Gatenby RM, Doloksaribu M, Bradford GE, Romjaii GE, Batubara L, Mirza I. 1995. Reproductive performance of sumatera and hair sheep crossbred ewes. SR-CRSP Annual Report 1994 - 1995, Sungai Putih, Sumatera Utara. González L, Moreno T, Bispo E, Dugan MER, Franco D. 2014. Effect of supplementing different oils: Linseed, sunflower and soybean, on animal performance, carcass characteristics, meat quality and fatty acid profile of veal from “Rubia Gallega” calves. Meat Science. 96 (2): Part A. https://doi.org/10.1016/j.meatsci.2013.09.027 Hendri. 1986. Studi perbandingan distribusi perdagingan kambing kacang dan domba priangan pada dua tingkat umur. Karya Ilmiah. Fakultas Peternakan. Institut Pertanian Bogor. Herman R. 1993. Perbandingan pertumbuhan komposisi tubuh dan karkas antara domba Priangan dan Ekor Gemuk. [disertasi]. Fakultas Pasca sarjana. Institut Pertanian Bogor. Bogor. Lambuth TR, Kemp JD, Glimp HA. 1970. Effect of rate of gain a slaughter weight on lamb carcass composition. Journal of Animal Science. 30: 27-35. Marinova P, Banskalieva, VS Alexandrov, Tzvetkova S, Stanchev V. 2001. Carcass Composition and meat qulity of kids fed sunflower oil supplemented diet. Small Rumminant Resources. 42 (3): 217-22. https://doi.org/10.1016/S0921-4488(01)00245-0. Mir PS, McAllister TA, Zaman S, Morgan Jones, SD, He ML, Aalhus JL, Jeremiah LE, Goonewardene LA, Weselake RJ and Mir Z. 2003. Effect of dietary sunflower oil and vitamin E on beef cattle performance, carcass characteristics and meat quality. Canada Journal of Animal Science. 83: 53–66 Morgado E, Ezequiel JMB, Galzerano L, Sobrinho S. 2013. Performance and carcass characteristics of lambs fed with carbohydrate sources associated to sunflower oil. Bioscience Journal. 29 (3): 712-720 Purbowati E, Sutrisno CI, Baliarti E, Budhi SPS, Lestariana W. 2006. Karakteristik fisik otot longissimus dorsi dan biceps femoris domba lokal jantan yang dipelihara di pedesaan pada bobot potong yang berbeda. Jurnal Protein. 13(2):147-153 Rasmani. 2010. Komposisi fisik dan potongan komersial karkas domba lokal jantan pada tingkat kecepatan pertumbuhan yang berbeda dengan pemeliharaan secara intensif. Bogor (ID): IPB. Rousset-Akrim S, Young OA, Berdague JL. 1997. Diet and growth effects in panel assessment of sheepmeat odour and flavour. Meat Science. 45:169-181. Supriyati. 2012. Pertumbuhan kambing Peranakan Etawah prasapih yang diberi susu pengganti. Jurnal Ilmu Ternak dan Veteriner. 17(2): 142-151. Rahayu, S, Astuti DA, Satoto KB, Priyanto R, Khotijah L , Suryati T, Baihaqi M 2011. Produksi domba balibu UP3 Jonggol melalui strategi perbaikan pakan berbasis Indigofera sp. dan limbah tauge. Laporan Penelitian Unggulan Fakultas. IPB, Dirjendikti Kementrian Pendidikan Nasional. Radunz, AE, Wickersham LA, Loerch SC, Fluharty FL, Reynolds CK, and Zerby HN. 2009. Effects of dietary polyunsaturated fatty acid supplementation on fatty acid composition in muscle and subcutaneous adipose tissue of lambs. Journal of Animal Science. 87: 4082-4091. Wiryawan KG, Astuti DA, Priyanto R, Suharti S. 2009. Optimalisasi pemanfaatan rumput dan legum pohon terhadap performa, produksi, dan kualitas daging domba jonggol. Laporan Penelitian. Bogor (ID): Fakultas Peternakan IPB